2008
DOI: 10.1074/jbc.m710222200
|View full text |Cite
|
Sign up to set email alerts
|

Coordinated Activation of the Nuclear Ubiquitin Ligase Cul3-SPOP by the Generation of Phosphatidylinositol 5-Phosphate

Abstract: Phosphoinositide signaling pathways regulate numerous processes in eukaryotic cells, including migration, proliferation, and survival. The regulatory lipid phosphatidylinositol 4,5-bisphosphate is synthesized by two distinct classes of phosphatidylinositol phosphate kinases (PIPKs), the type I and II PIPKs. Although numerous physiological functions have been identified for type I PIPKs, little is known about the functions and regulation of type II PIPK. Using a yeast two-hybrid screen, we identified an interac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
74
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(79 citation statements)
references
References 38 publications
4
74
0
1
Order By: Relevance
“…The experiments described above are in agreement with those of Bunce et al, who demonstrated Pcif1-mediated ubiquitination of Pdx1 in an overexpression system (34). To determine whether endogenous Pcif1 regulates Pdx1 protein levels in β cells, we next examined the impact of Pcif1 loss of function on Pdx1 protein accumulation in Min6 mouse insulinoma cells.…”
Section: Pcif1 Targets Pdx1 For Ubiquitination By a Cul3-based E3 Ubisupporting
confidence: 74%
“…The experiments described above are in agreement with those of Bunce et al, who demonstrated Pcif1-mediated ubiquitination of Pdx1 in an overexpression system (34). To determine whether endogenous Pcif1 regulates Pdx1 protein levels in β cells, we next examined the impact of Pcif1 loss of function on Pdx1 protein accumulation in Min6 mouse insulinoma cells.…”
Section: Pcif1 Targets Pdx1 For Ubiquitination By a Cul3-based E3 Ubisupporting
confidence: 74%
“…SPOP contains two conserved domains: an N-terminal MATH (Meprin and Traf Homology) domain that recruits substrate proteins, and a C-terminal BTB (Bric-a-bracTramtrack-Broad complex) domain that interacts with Cul3 (17,18). Somatic heterozygous missense SPOP mutations, clustered in the MATH domain (Fig.…”
mentioning
confidence: 99%
“…PtdIns5P levels are then regulated either by inhibition of PIPKII␤ (such as in stress responses where p38 MAPK phosphorylates PIPKII␤) (522) or by stimulation of the type I PtdIsn(4,5)P 2 4-phosphatase (1833). Another mechanism by which PIPKII␤ and PtdIns5P regulates nuclear functions is the association of the kinase with a nuclear ubiquitin ligase, Cul3-SPOP and stimulation of its activity (198).…”
Section: Nucleusmentioning
confidence: 99%